2010
DOI: 10.1002/jobm.201000097
|View full text |Cite
|
Sign up to set email alerts
|

Water‐soluble red pigments from Isaria farinosa and structural characterization of the main colored component

Abstract: The present study describes the red pigment synthesized by the filamentous fungi Isaria farinosa under submerged culture conditions. The pigment production was optimal under the following conditions: pH 5, agitation speed 150 rpm, temperature 27 °C, incubation time 192 h, light source total darkness, sucrose and glucose as carbon source, yeast extract, meat peptone and monosodium glutamate at a fixed concentration of 3% as nitrogen source. The addition of 10 mM CaCl 2 to the culture medium increased the biomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…Cordyceps farinosa Anthraquinone derivative [73] Ophiocordyceps unilateralis (Formerly Known as Cordyceps unilateralis)…”
Section: Monascus Speciesmentioning
confidence: 99%
See 2 more Smart Citations
“…Cordyceps farinosa Anthraquinone derivative [73] Ophiocordyceps unilateralis (Formerly Known as Cordyceps unilateralis)…”
Section: Monascus Speciesmentioning
confidence: 99%
“…(Figure 8b) [25]. Also, the genera belonging to the family Cordycipitaceae such as Torrubiella, Cordyceps, Beauveria, Hyperdermium, and Lecanicillium have been revealed to be promising producers of bioactive pigments, e.g., tenellin and bassianin are reported from Beauveria bassiana and Beauveria brongniartii (formerly known as Beauveria tenella), pyridovericin and pyridomacrolidin from Beauveria bassiana, torrubiellones A-D from the genus Torubiella, oosporein from Lecanicillium aphanocladii, whereas anthraquinone-related compounds are reported from Cordyceps farinosa (formerly known as Isaria farinosa) (Figure 9a) [41,[73][74][75]125]. Similarly, the pigments erythrostominone, 4-O-methyl erythrostominone, deoxyerythrostominone, deoxyerythrostominol, epierythrostominol, and 3,5,8-TMON (3,5,8-trihydroxy-6-methoxy-2-(5-oxohexa-1,3-dienyl)-1,4-naphthoquinone) have been reported from Ophiocordyceps unilateralis (formerly known as Cordyceps unilateralis), and skyrin from Hyperdermium bertonii (Figure 9a) [25].…”
Section: Fungal Species Pigments Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, too little cell inoculum will result in sluggish growth and inefficient nutrient utilization. Velmurugan et al (2010a) also reported that spore inoculum concentration of 4 ml containing 6×10 5 spores/ml was the best for inoculation of 5 g of substrate for solid state fermentation. General et al (2014) reported optimum inoculum volume of 1.8×10 6 spores per gram solid substrate during pigment production by Talaromyces amestolkiae using macroalgal biomass as the substrate.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a red pigment produced by a strain of Isaria farinosa was recently elucidated as a chromophore of the anthraquinone type 105 . Similarly, the red pigment produced by Paecilomyces sinclairii, which was beforehand discovered but uncharacterized 106 , is certainly of an identical chemical nature, i.e. an amino group linked to an anthraquinone structure 105 .…”
Section: Kerriamentioning
confidence: 98%